2015
DOI: 10.1111/jfbc.12116
|View full text |Cite
|
Sign up to set email alerts
|

Identification of β-Glucosidase Activity of L actobacillus plantarum  CRNB22 in Kimchi and Its Potential to Convert Ginsenoside Rb1 from P anax Ginseng

Abstract: This study involved isolating lactic acid bacteria (LAB) that exhibit β-glucosidase activity from kimchi and examining the hydrolytic activity of the enzyme on saponin. Of the 28 types of LAB found in Korean kimchi that 6 strains exhibited positive β-glucosidase activity based on the esculin iron agar test, only CRNB22 strain was able to hydrolyze ginsenoside Rb1. The crude enzyme from this kimchi LAB strain showed strong ability to convert ginsenoside Rb1 into Rg3 and Rg5. This isolated strain was identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
1
6
0
1
Order By: Relevance
“…During a typical lactic acid fermentation, the pH decreases while acidity increases [ 1 , 21 , 22 ]. This finding has also been reported during the lactic acid fermentation of ginseng and/or red ginseng [ 11 , 18 , 23 ], and was corroborated by our results.…”
Section: Resultssupporting
confidence: 93%
“…During a typical lactic acid fermentation, the pH decreases while acidity increases [ 1 , 21 , 22 ]. This finding has also been reported during the lactic acid fermentation of ginseng and/or red ginseng [ 11 , 18 , 23 ], and was corroborated by our results.…”
Section: Resultssupporting
confidence: 93%
“…Leuconostoc mensenteroides WiKim19 and Pediococcus pentosaceus WiKim20 with β-glucosidase activity isolated from kimchi had a greater ability to transform ginsenoside Rb1 into ginsenosides Rg3 and Rg5 than the other strains [ 28 ]. In addition, Lactobacillus plantarum CRNB22 with β-glucosidase activity isolated from kimchi converted ginsenoside Rb1 into ginsenosides Rg3-s, Rg3-r, and Rg5 [ 29 ]. Depending on the enzyme type and experimental conditions, the final conversion of ginsenoside Rb1 was into Rd, Rg3, compound K, and other compounds [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Under the above optimal conditions for 14 d, 3.794±0.061 mg/mL of ginsenoside Rb 1 was fully hydrolyzed by crude enzyme of strain MBT213, and was released 0.110±0.01 mg/mL ginsenoside Rd ( Table 2 ). On the other hand, in a study of isolation of Lactobacillus plantarum CRNB22 and its screening of LAB exhibiting β-glucosidase activity from Kimchi ( Renchinkhand et al , 2015 ), observed that ginsenoside Rb 1 was hydrolyzed under optimum condition (pH 6.0 or 7.0 at 35°C) for 7 d. In addition, under these optimal conditions, the crude enzyme obtained from CRNB22 converted the ginsenoside Rb 1 to Rg 3 (epimer S/R) and Rg 5 . After 7 d of hydrolysis, ginsenoside Rb 1 was decreased from 1.019 mg to 0.773 mg, and then converted to 0.135 mg Rg 3 -S, 0.038 mg Rg 3 -R, and 0.072 mg Rg 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Of these methods, enzymatic conversion is the most desirable one for production of particular ginsenosides ( Kim et al , 2005 ). β-glucosidase produced by various microorganisms such as Lactobacillus plantarum CRNB22 ( Renchinkhand et al , 2015 ), Enterococcus faecalis CRNB-A3 ( Renchinkhand et al , 2016 ) and Microbacterium sp. ( Cheng et al , 2008 ) has been used for the production of biotransfomed ginsenosides.…”
Section: Introductionmentioning
confidence: 99%